The relationship between social intelligence managers with job satisfaction of teachers in schools - Akbar Rezaei; Ahad Khalilzadeh (Islamic Azad University, Tabriz Branch, 2009)
The main purpose of this study investigated the relationship between social intelligence managers with job satisfaction of teachers in districts north of West Azerbaijan province was 89-88 academic year.The study of all the teachers، administrators and city north of West Azerbaijan province in the academic year 89-88 comprised using stratified random sampling number of 12 principal and 36 teachers were selected as sample. Data from two questionnaires Tromso social intelligence and job satisfaction Fild and Ruth were used. Data using statistical Correlation and Multiple Regression were analyzed. The results showed that: between social intelligence managers and job satisfaction of teachers and significant direct relationship exists. Between the components of intelligence and social service managers and job satisfaction of teachers has a direct and meaningful relationship. Social Skills and Social Information Processing components are the best prediction of teacher Job Satisfaction.